PENGARUH KOMORBID HIPERTENSI TERHADAP SAVERITAS PASIEN COVID-19 DI RUMAH SAKIT TNI AL DR.F.X SUHARDJO AMBON - Sitti R Latuamury; Petra Selvia Ruban; Dwight Nusawakan (STIKES Pasapua Ambon, 2022)
Introduction:. The severity of Covid-19 is affected by endurance, age, and several comorbid diseases, one of which is hypertension. Hypertension is a collection of progressive cardiovascular symptoms and can kill silently Purpose: To Know the Effect of Comorbid Hypertension on the Severity of Covid-19 Patients at TNI Al Dr.F.X Suhardjo Hospital Ambon. Method: This study uses a retrospective research type. Population and the sample, namely the total number of patients confirmed positive for Covid-19 with comorbid hypertension at TNI Al Dr.F.X Suhardjo Ambon Hospital, totaled 25 people. The test uses a Simple Linear Regression test. Results: Most of the respondents had comorbid hypertension categorized as hypertension degree I by 14 respondents (56%) and hypertension degree II by 11 respondents (56%) and severity of Covid-19 in the category of mild disease by 16 respondents (64%) and severe disease by 9 respondents (36%). Regression Correlation test results Simple Linear obtained a calculated t value of 2.846 and a significance value of 0.009 <0.05. So that the hypothesis in the study can be concluded that there is an effect of comorbid hypertension on the severity of Covid-19 patients at the TNI Al Dr.F.X Suhardjo Hospital Ambon. Conclusion: There is an effect of comorbid hypertension on the severity of Covid-19 patients at the TNI Al Dr.F.X Suhardjo Hospital Ambon. Suggestion: It is expected to improve services for Covid-19 patients with hypertension. Considering that patients with Covid-19 with hypertension have a fairly serious level of severity